Long-term physical, chemical and biological changes in a small, urban estuary. Issue 1 (22nd April 2016) - Viskich, M; Griffiths, CL; Erasmus, C; Lamberth, S
Abstract : The Diep River estuary, a small estuary in suburban Cape Town, South Africa, has been subject to disturbance for centuries. Several earlier studies have documented conditions in the system, providing baselines against which to measure more recent changes. This study: (i) describes major physical and hydrological changes that have occurred within this estuary; (ii) documents faunistic changes subsequent to earlier biological surveys; and (iii) provides an up-to-date faunal list. Salinity measurements and both invertebrate and fish samples were taken at five stations along the estuary in summer and winter 2014. A census of sandprawn Callichirus kraussi densities was also undertaken to compare with earlier surveys. Developments within the Diep River catchment and estuary have resulted in extensive changes in flow and salinity regimes, causing marked reductions in summer salinity levels, changes in frequency of mouth closure, and deteriorations in water quality. These have resulted in major changes in faunal composition and distribution, including an increase in numbers of non-indigenous species. Surveys in the early 1950s recorded 47 invertebrate species, whereas only 23 were found in 1974. A total of 23 species were again recorded in 2014, but these included several freshwater forms not previously reported, which had entered the system due to lowered salinity values, as well as new alien introductions. Only six of the 69 taxa recorded were reported by all three surveys. There have been substantial declines in sandprawn abundance, from 40 million in 1998 to just over 12 million in 2014. In all, 12 fish species were recorded in the 1950s, nine in 1974, but only five in 2014, including the newly detected invasive mosquito fish Gambusia affinis and the translocated tilapia Tilapia sparrmanii . Thus, only three of the original native fish species remain. Contrary to these losses, the present bird fauna appear to be more abundant and diverse than previously. Regular monitoring is recommended to obtain a clearer understanding of ongoing changes, and major management interventions will be needed if further degradation is to be prevented.